Flexibilização das convenções coletivas do trabalho na tríplice fronteira: Brasil, Paraguai e Argentina - Dominguesck, Junior (2017)
The present study addresses the flexibilization of collective labor conventions in the triple frontier.Objective to present to the reader the general, social and legal aspects, through bibliographical research, with doctrinators and legislation, pertinent to the theme.This paper was developed on the Tri-Border area (Brazil, Argentina and Paraguay), which is formed by the following cities: on the Brazilian side, Foz do Iguassu, on the Argentinian side there is the city of Puerto Iguazu, and, finally, on the Paraguaian side, Ciudad del Este. Its area is 2500 square kilometers (965 square miles), of which the Brazilian city is the largest.The region is considered very important for the three countries. One can mention the largest hydroelectric plant in energy production, the result of a partnership between Brazil and Paraguay, the Iguassu Falls, one of the seven natural wonders of the world, located on the border of Brazil and Argentina, besides the commerce of electronics in Ciudad del Este, which the world’s third largest sales center. Today, Paraguay is the largest exporter of electricity in MERCOSUR. Moreover, the country stands out as the only country under the EU-GSP, awarded by the European countries in 2014. This is reflected in more than 9700 Paraguayan products that can be exported to the European market with import duty exemption. Nowadays, there are about two million people circulating between countries. Foz do Iguassu is very important for the Brazilian trade balance, as it accounts for 6.5% of exports on its own. The region is predominantly a tourist destination, and this master’s thesis, which was written in loco, aims at analysing the evolution conditions as well as the labor law flexibility on the Tri-Border area in a comparative study.The back-and-forth movement of people is common in term papers, however, theory and practice do not always go together, mainly when it refers to the workers’ rights in the countries on this research. Under the focus on which this paper was developed, the rights established on the MERCOSUR agreement were also studied, in order to understand if they are respected in practice, if there are any gains for the working class in the collective agreements in the region, and where the workers’ right is higher.Throughout this paper, we present the Maquila Paraguayan law. In spite of not being so young, the present federal management has struggled to bring benefits from this law in practice. In the body of this paper, we foccused on the flexibility of the border laws, which proved the Paraguayan and the Brazilian material rights to be the bigger. As previously mentioned, the region is a tourist destination but we chose the commerce agreements, as they are richer in discussions about gains or about the lack of them. It is said that the major rule that comes from the Labor Law is the collective bargaining, and this paper aims at this item, since it verifies whether it really exists in practice. Thus, collective bargaining was analyzed, establishing a study of foreign legislations, the norms of Paraguay and Argentina, and drawing them, with the Brazilian ones, on the triple border.